A survey of innovative teaching approaches in the University of the Philippines elementary school - Ratanasee, Ketsuda 1941- (s.n], 1974)
The innovative teaching approaches used in the University of the Philippines Elementary School were identified in this study. Its implications for Thailand were derived.